2016
DOI: 10.1109/tetc.2015.2389661
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Wideband Delphi Method to Study State Cyber-Defence Requirements

Abstract: Background-Edward Snowden's revelations of the extensive global communications surveillance activities of foreign intelligence services have led countries such as Indonesia to take concrete steps to enhance protective information security for classified data and communications. Objective -This paper develops the Wideband Delphi Method to study the Indonesian Government's requirements for cyber-defence in response to reported secret intelligence collection by the Australian Signals Directorate (ASD). It provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Understanding the perceived threats can drive security requirements. Thus, security requirements play an important role in mitigating threats, such as unauthorised disclosure data by foreign intelligence services [19,35]. However, our participants confirmed that understanding the government security requirements was essential in offering trustworthy services to the GAs.…”
Section: Government-specific Security Requirementsmentioning
confidence: 74%
See 3 more Smart Citations
“…Understanding the perceived threats can drive security requirements. Thus, security requirements play an important role in mitigating threats, such as unauthorised disclosure data by foreign intelligence services [19,35]. However, our participants confirmed that understanding the government security requirements was essential in offering trustworthy services to the GAs.…”
Section: Government-specific Security Requirementsmentioning
confidence: 74%
“…However, we only conducted interviews and individual feedback with six participants (n=6) from two selected SPs. The two providers are the major SPs in Indonesia, and their network infrastructures were reported to be compromised according to Edward Snowden's revelations in 2013 [19].…”
Section: Data Collection: a Three-round Delphi Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Related to national cyber security defense, other studies conducted by Yudishthira. He identified mitigation controls in relation to the five defence in depth elements: people, operations, technology, governance and legal remedies for state cyber defense [6].…”
Section: Introductionmentioning
confidence: 99%